The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jpm13060915
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome in Parkinson’s Disease

Abstract: Background: Restless legs syndrome (RLS) might worsen sleep quality and quality of life in people with Parkinson’s disease (PwPD). Objective: The main aim of the present study is to explore the associations between RLS and sleep, quality of life and other non-motor symptoms (NMS) in a sample of PwPD. Methods: We compared the clinical features of 131 PwPD with and without RLS, in a cross-sectional study. We used several validated scales for assessment: the International Restless Legs Syndrome Study Group rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Various comorbidities such as kidney disease, cardiovascular diseases, obstructive lung disease, diabetes mellitus, hypothyroidism, chronic liver disease, and neurological, rheumatological and respiratory disorders may accompany RLS [ 2 , 16 , 17 , 18 , 19 , 40 ]. In a cross-sectional study including 5324 subjects, high cholesterol and hypertension were associated with RLS [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various comorbidities such as kidney disease, cardiovascular diseases, obstructive lung disease, diabetes mellitus, hypothyroidism, chronic liver disease, and neurological, rheumatological and respiratory disorders may accompany RLS [ 2 , 16 , 17 , 18 , 19 , 40 ]. In a cross-sectional study including 5324 subjects, high cholesterol and hypertension were associated with RLS [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RLS could be deficient in vitamins D and B12 [ 14 , 15 ]. Various comorbidities such as kidney disease, cardiovascular diseases, diabetes mellitus, hypothyroidism, chronic liver disease, and neurological, rheumatological and respiratory disorders accompany RLS [ 2 , 16 , 17 , 18 , 19 ]. In our recent study, a significantly higher number of amalgam dental fillings were found in older adults with RLS as compared to the subjects without RLS symptoms [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certain conditions, such as iron deficiency, anemia, pregnancy, end-stage renal disease, diabetes mellitus, and peripheral neuropathy, can exacerbate or contribute to RLS. Many neurodegenerative diseases, including Parkinson's disease, spinocerebellar ataxias, Huntington's disease, and hereditary spastic paraparesis, have been associated with a higher occurrence of RLS [209][210][211][212]. So far, only four studies assessed this non-motor symptom in ALS patients [213][214][215][216].…”
Section: Restless Legs Syndromementioning
confidence: 99%
“…There may also be accompanying movements as a result of patients trying to relieve their discomfort which is important information that may aid clinical diagnosis. The reported prevalence of RLS is around 50 % in PD population studies [115] , [116] , [117] , [118] . The diagnosis of RLS in PD, as in the general population, is based primarily on clinical interview and evaluation but this can be supplemented with the sensory component of the suggested immobilisation test (SIT) test showing an increase in sensory leg discomfort [109] , [119] .…”
Section: Periodic Limb Movement During Sleep and Restless Leg Syndromementioning
confidence: 99%